Kualifikasi Da’i: Sebuah Pendekatan Idealistik dan Realistik - Aliyudin Aliyudin (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2015)
Preacher in terms of expertise is divided into two, first, in general is every Muslim preachers who mukalaf (adult). Obligations of propaganda has been inseparably attached to them according to their respective capabilities as the realization of the Prophet commands to convey Islam to everyone even if only one paragraph. Secondly, specifically preachers are Muslims who have taken specialization (mutakhashish) in Islam, namely the clergy and so on. In this regard there are two approaches to determine qualification preachers. First, idealistic approach to the special preachers, preachers in this context must be qualified scientific, spiritual, and mental or moral qualified or adequate. Secondly, realistic approach to the general preachers, in this context propaganda as fard ayn, Every Muslim is obliged to preach in various forms and ways according to their respective capabilities, although only knows one verse.